Association of MyoD1 Gene Polymorphisms with Meat Quality Traits in Domestic Pigeons (Columba livia) - Xinyang Dong; Haiyue Cao; Haiguang Mao; Qihua Hong; Zhaozheng Yin (The Journal of Poultry Science, 2019)
Myogenic differentiation 1 (MyoD1) belongs to the MyoD family and plays a key role in myogenesis and consequently, in determining muscle fiber characteristics. In this study, single nucleotide polymorphisms (SNPs) in the exons of MyoD1 were identified in 200 domestic pigeons (Columba livia) by direct DNA sequencing, and the association between MyoD1 polymorphisms and meat quality traits was analyzed. We found four novel variations (A2967G, G3044A, A3164C, and C3311G) in exon 3. The SNP A2967G is a synonymous mutation, while the other 3 SNPs are located in the 3′ untranslated region. The analysis revealed 3 genotypes, in which allele A was the predominant allele in the SNP A2967G, while allele B was the predominant allele in the SNPs G3044A and A3164C. The mutations A2967G and G3044A were significantly associated with meat quality traits in pigeon. Pigeons with AA or AB genotypes had higher breast muscle concentrations of inosinic acid and intramuscular fat than those of BB genotype. Moreover, these 2 SNPs had significant effects on MyoD1 mRNA expression. The SNPs A2967G and G3044A were organized into 4 haplotypes, which formed 7 diplotypes. Association analysis showed that the diplotypes were not significantly associated with meat quality traits. Our results implied that associations do exist between MyoD1 gene polymorphisms and meat quality traits in domestic pigeons, and the AA and AB genotypes could be applied as genetic markers in marker-aid pigeon breeding.